"Occipital Pole" Sign on 18F-FDG PET for Dementia With Lewy Bodies and Posterior Cortical Atrophy: Evidence From the Treviso Dementia (TREDEM) Registry. (27th September 2022) - Gallucci, Maurizio; Fiore, Vittorio; Grassivaro, Francesca; Da Ronch, Chiara; Bonanni, Laura
Abstract: The 18 F-FDG PET images of dementia with Lewy bodies and posterior cortical atrophy, a visual-cognitive phenotype described in patients with Alzheimer disease, show occipital lobe hypometabolism with relative sparing of the primary visual cortex (PVC) generating the "occipital tunnel" sign proposed by Sawyer and Kuo in 2017, which is viewable on the medial sagittal projection. We believe that the saving of PVC compared with the lateral occipital cortex can be better appreciated by capturing the posterior projection of the PVC in a 3D stereotactic surface projection map, and we propose the name of "occipital pole" sign for this evidence.